Tropical Montane Forest Conversion Is a Critical Driver for Sediment Supply in East African Catchments - Stenfert Kroese, J.; Jacobs, S.R.; Tych, W.; Breuer, Lutz; Quinton, J.N.; Rufino, Mariana C. (American Geophysical Union, 2020)
Land use change is known to affect suspended sediment fluxes in headwater catchments. There is however limited empirical evidence of the magnitude of these effects for montane catchments in East Africa. We collected a unique 4-year high-frequency data set and assessed seasonal sediment variation, water pathways, and sediment response to hydrology in three catchments under contrasting land use in the Mau Forest Complex, Kenya's largest tropical montane forest. Annual suspended sediment yield was significantly higher in a smallholder agriculture-dominated catchment (131.5 ± 90.6 t km−2 yr−1) than in a tea-tree plantation catchment (42.0 ± 21.0 t km−2 yr−1) and a natural forest catchment (21.5 ± 11.1 t km−2 yr−1) (p < 0.05). Transfer function models showed that in the natural forest and the tea-tree plantations subsurface flow pathways delivered water to the stream, while in the smallholder agriculture shallow subsurface and surface runoff were dominant. There was a delayed sediment response to rainfall for the smallholder agriculture and the tea-tree plantations. A slow depletion in sediment supply suggests that the wider catchment area supplies sediment, especially in the catchment dominated by smallholder farming. In contrast, a fast sediment response and depletion in sediment supply in the natural forest suggests a dominance of temporarily stored and nearby sediment sources. This study shows that the vegetation cover of a forest ecosystem is very effective in conserving soil, whereas catchments with more bare soil and poor soil conservation practices generated six times more suspended sediment yield. Catchment connectivity through unpaved tracks is thought to be the main explanation for the difference in sediment yield.